Innovative Interpretations: Three Recent Studies by Latin American Women Scholars - David William Foster (Mistral, 2021)
This article offers a survey of recent work by women scholars in the field of Latin American Studies. Focusing on the writings of Emily Hind, Ana Forcinito, and Sophia Beal, it identifies dominant threads in their research into masculinity and canon formation in Mexico, women filmmakers in Argentina, poetics of memory in Uruguay, and gender and urban spatiality in Brazil. Set within a larger context of the history of Gender Studies within the discipline, this piece provides a vision of pioneering developments in contemporary Latin American Cultural Studies.